Spiritualitas Sosial Tarekat Naqsabandiyah: Kajian terhadap Prinsip Khalwat Dar Anjuman - Fuady Abdullah (TSAQAFAH, 2018)
When looking at the teachings of sufism, the journey to seek spirituality is often colored by reproducing dzikr and doing seclusion. This gives the view that the spirituality in sufism rely heavily on individualism and the release of any social bonds. Hence, followers of sufism should put a distance between them and their surrounding community and even their family to avoid negative influences during their self-purification. From here, a later view emerges that the teachings of sufism tend to be distant and indifferent to any social, cultural, economic, and political issues and do not have a positive contribution to the welfare of society. This vie w is not in accordance with the views of some followers of sufism. This view can be refuted by proposing one of the main concepts in the Naqshbaniyyah order, namely the principle of khalwat dar anjuman (seclusion in the crowd). By examining some of the writings that became the reference of this order to understand its meaning, it can be found that the concept is interpreted in various ways and has a wide spectrum of applications. From the watchfulness of dzikr which signifies the pressence of the heart with God even when in crowded places until the obligation of a sufi to interact actively with his society. Spirituality and social activism are not contradictory, but they fill and support each other. It can be seen later that this teaching can offer a concept to be a model of social spiritual life that is compatible to be applied in modern times to achieve and maintain one’s spirituality and at the same time to contribute to the benefit of those around him.